Central precocious puberty in boys; diagnosis, treatment and follow-up: a nation-wide study - Odabasi Gunes, Sevinc; Sakar, Merve; Muratoglu Sahin, Nursel; Karaguzel, Gulay; Cimbek, Emine Ayca; Darendeliler, Feyza; Cetinkaya, Semra (Springer, 2025)
Purpose To evaluate demographic characteristics, clinical, laboratory, imaging features, and treatment responses of boys who were diagnosed and treated for central precocious puberty (CPP). Methods The data were collected from pediatric endocrinology clinics in T & uuml;rkiye. Patients were classified into two groups based on magnetic resonance imaging (MRI) findings, idiopathic CPP (iCPP) and organic CPP (oCPP). The oCPP group was further cathegorized into three subgroups: oCPP-confirmed, oCPP-unrelated, and oCPP-uncertain lesions. Results Among 232 patients, 62.9% were diagnosed with iCPP. All patients aged <3 years had oCPP-confirmed lesions. Basal luteinizing hormone (LH) and total testosterone (T) levels were higher in oCPP group than in iCPP group (p = 0.004 and p = 0.02, respectively). Basal LH, basal follicle-stimulating hormone (FSH), T, and peak LH/FSH were lower in the iCPP-obese group (p < 0.05). T differed significantly among the oCPP-confirmed, oCPP-unrelated, and oCPP-uncertain subgroups (p = 0.032). Among patients that reached final height (FH), the difference between target height (TH) standard deviation score (SDS) and FH SDS was higher in oCPP group than in iCPP group (p < 0.05). A positive correlation was found between predicted adult height at the treatment initiation and FH (r = 0.463 p = 0.020). Factors affecting FH were height SDS at the beginning of treatment, paternal height SDS, and TH SDS. Conclusions The prevelance of oCPP was found lower compared with previous literature data. Currently, there is no reliable marker to predict oCPP that would allow clinicians to safely omit MRI in iCPP cases. However, boys under 3 years of age should be carefully evaluated for potential organic causes of CPP.
Keywords: Boys; Central precocious puberty; Gonadotropin-releasing hormone analog treatment; Final height